Analysis of gingival crevicular fluid biomarkers in patients with metabolic syndrome. (March 2022) - Nibali, Luigi; Stephen, Abish; Hagi-Pavli, Eleni; Allaker, Robert; Pino, Antonino Di; Terranova, Valentina; Pisano, Marcella; Marca, Salvatore Di; Ferrara, Viviana; Scicali, Roberto; Giordano, Mauro; Purrello, Francesco; et al.
Abstract: Objectives: To assess associations between gingival crevicular fluid (GCF) markers in patients with metabolic syndrome, with or without concomitant periodontitis. Methods: A total of 95 patients with Metabolic Syndrome (MetS) had a periodontal examination and gingival crevicular fluid samples taken. Proteomic analysis of gingival crevicular fluid (GCF) was carried out by Human XL Cytokine protein arrays in 12 selected patients, followed by multiplex ELISA of 11 analytes in 95 participants. Results: Increased levels of Aggrecan, IL-6 and IL-8 were found in patients with periodontal health compared with moderate and severe periodontitis. The inverse stepwise association between severity of periodontitis and reduced Aggrecan levels was also observed at adjusted linear regression analysis. Diagnosis of diabetes was associated with higher GCF levels of IL-8 and MMP-8. Conclusion: Diabetes may affect GCF levels of cytokines, irrespective of periodontal status. Periodontal status may be associated with Aggrecan levels in the GCF of patients affected by metabolic syndrome. Clinical significance: Investigation of GCF biomarkers may potentially help have diagnostic potential in patients with MetS.